Voicing the professional doctorate and the researching professional's identity: Theorizing the EdD's uniqueness (UCL Press, 2018)
Although there is increasing interest in how learning to become a researching professional is understood by students undertaking a professional doctorate of education (EdD), the topic remains under-researched and under-theorized. In this article, we provide a set of theorizations, starting with the purpose and distinctiveness of the professional doctorate and the researching professional identity as this is understood by students and staff participating in the EdD programme in one university in the United Kingdom (UK). This is followed by a retheorization of the researching professional as they develop a reflexive disposition to connect the workplace and the university as the subject and object of the same critical stance. We explore: how the professional doctorate may be understood as practices of diverse researching professionals at different phases and stages of their doctoral journey; the imperative of critical reflexivity as one moves from practitioner to researching professional; and the placing of 'practice' at the nexus of the workplace, the university (doctoral programme) and leading professional change. We conclude with a merging of theorizations building on the being and doing of reflexive practice by EdD doctoral educators/supervisors and doctoral students/researching professionals. Our theorizations are drawn from insights arising from recent EdD research projects (Burnard et al., 2016; Burnard et al., 2018; Heaton et al., forthcoming), and highlighted by narratives from two EdD students currently on a part-time EdD programme.